Characteristics of Transient Eddies During Ural Blocking Events With Different Lifetime in Winter - Zhang, Jinyu; Li, Yan; Wang, Zhilan; Zhang, Yu; Lu, Yao (Frontiers in Earth Science, 2022)
Ural blocking high (hereafter UB) is one of the most important weather systems influencing the weather and climate of China, with its onset and development closely connected with transient eddies. Herein, we classified the wintertime UB events during 1979-2015 into three types according to their lifetime, i.e., short, medium, and long lifetime UB events and further analyzed the characteristics of momentum and heat fluxes transported by transient eddies during the three types of UB events. The results show that the eddy momentum and heat transport by transient eddies over the Ural regions is strong, while the westerly is weak, favorable for the establishment and maintenance of the UB. Before the onset of all the UB events there are enhanced lower-level temperature disturbances, decelerated westerly and convergence of transient momentum and heat fluxes. After the onset of the UB, the upper-level jet stream is accelerated and eddy flux convergence is enhanced. Furthermore, it is found that the duration and position of convergence could be one of important factors determining the lifetime of UB event. The long-time strong convergence of transient eddies favors the maintenance of UB. During long UB events, the polar jet and the convergence of eddy momentum fluxes have the strongest intensity and northward shifted position. The convergence is further strengthened until Day +2 and weakened since Day +7, favorable for the long-time maintenance of UB. There is convergence on Day -3 of both short and medium UB events, which disappears on Day +4 during short events, while strengthened after the onset of medium events, leading to a long-time maintenance of UB. Furthermore, among the three types of UB events, the upward propagation of wave activity and E-P flux divergence are the strongest and most long-lasting during long UB events, while the weakest and shortest during short UB events, which can also verify strong atmospheric baroclinicity and long-lasting strong convergence of transient eddies are favorable for long duration of the UB.